2023
DOI: 10.1039/d3sc01647a
|View full text |Cite
|
Sign up to set email alerts
|

Composite polymer electrolytes with ionic liquid grafted-Laponite for dendrite-free all-solid-state lithium metal batteries

Abstract: Composite polymer electrolytes (CPEs) with high ionic conductivity and favorable electrolyte/electrode interfacial compatibility are promising alternatives to liquid electrolytes. However, severe parasitic reactions in the Li/electrolyte interface and the air-unstable...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Ionic liquids (ILs), characterized by low-melting-point-based molten salts composed of self-dissociated cations and anions, have negligible vapor pressure, nonflammability, environmental friendliness, electrochemical stability, and high ionic conductivity, which can ameliorate the risks caused by LEs . Based on this, researchers have demonstrated that the incorporation of ILs into the polymer matrix as a plasticizer can impart notable improvements in the ionic conductivity by reducing the crystallinity of the polymer, enhancing flexibility, and strengthening the chain segment motion. , In addition, ILs have been incorporated into diverse inorganic porous frameworks, effectively inhibiting the growth of Li dendrites due to the high hardness of the inorganic frameworks, and playing a role in regulating Li + deposition through various interactions …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ionic liquids (ILs), characterized by low-melting-point-based molten salts composed of self-dissociated cations and anions, have negligible vapor pressure, nonflammability, environmental friendliness, electrochemical stability, and high ionic conductivity, which can ameliorate the risks caused by LEs . Based on this, researchers have demonstrated that the incorporation of ILs into the polymer matrix as a plasticizer can impart notable improvements in the ionic conductivity by reducing the crystallinity of the polymer, enhancing flexibility, and strengthening the chain segment motion. , In addition, ILs have been incorporated into diverse inorganic porous frameworks, effectively inhibiting the growth of Li dendrites due to the high hardness of the inorganic frameworks, and playing a role in regulating Li + deposition through various interactions …”
Section: Introductionmentioning
confidence: 99%
“…25 Based on this, researchers have demonstrated that the incorporation of ILs into the polymer matrix as a plasticizer can impart notable improvements in the ionic conductivity by reducing the crystallinity of the polymer, enhancing flexibility, and strengthening the chain segment motion. 26,27 In addition, ILs have been incorporated into diverse inorganic porous frameworks, effectively inhibiting the growth of Li dendrites due to the high hardness of the inorganic frameworks, and playing a role in regulating Li + deposition through various interactions. 28 In this study, a bio-inspired GPE was proposed by combining polydopamine-modified zeolitic imidazolate framework-90 (ZIF-90@PDA) and an in situ cross-linked polymer m a t r i x w i t h 1 -e t h y l -3 -m e t h y l i m i d a z o l i u m b i s -[(trifluoromethyl)sulfonyl]imide ([EMIM][TFSI]) and fluoroethylene carbonate (FEC).…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Furthermore, the signicant volume change (∼76%) that occurs during the conversion of sulfur to lithium sulde brings about severe electrode cracking, leading to poor battery cycle life. [15][16][17][18] To mitigate the aforementioned issues, researchers have developed various strategies in terms of separators, carbon hosts, catalysts, and binders. [19][20][21][22][23][24] Polyvinylidene uoride (PVDF), a synthetic polymeric binder, is commonly used in lithium-sulfur batteries due to its good chemical, thermal stability as well as its excellent ability to bind conductive materials such as carbon black and Super P via hydrophobic interactions.…”
Section: Introductionmentioning
confidence: 99%